Intraday return of winners vs losers: Indonesian capital market evidence - Masyhuri Hamidi; Fajri Adrianto; Nanda Nanda; Eko Dwi Putra; Amer Azlan Abdul Jamal (Universiti Malaysia Sarawak, 2024)
The aim of this study is to determine intraday returns in the Indonesian capital market, using sample of 177 listed Indonesian companies from 2021-2022. This study adopts a multiple linear regression analysis, where the return of the last half hour as an endogenous variable consists of winners and losers, the return of the first half hour of trading, the volume of the first half hour, overnight returns, and the USA index futures as an exogenous variable. The originality of this research aims to demonstrate empirical evidence on intraday returns by distinguishing winner & loser stocks and the relationship between the intraday returns of winners and losers with volume, overnight, and US index futures in the emerging market (Indonesia). We find that the first half hour of trading can impact future return. The return of the first thirty minutes is significantly positive on the return of the last thirty minutes for both winner and loser stocks. Further, the volume of the first half hour and the overnight return both positively influences on the last half hour return of the day for loser stocks. This study can offer valuable insights for investment portfolio strategies, especially regarding intraday returns. The findings of this research prove to be a valuable resource for investors when devising investment strategies in the stock market. Additionally, it provides guidance for regulators in establishing rules for stock trading, particularly in transactions involving trading robots.